2018
DOI: 10.1002/macp.201700572
|View full text |Cite
|
Sign up to set email alerts
|

Tuned Surface and Mechanical Properties of Polymeric Film Prepared by Random Copolymers Consisting of Methacrylate‐POSS and 2‐(Methacryloyloxy)ethyl Phosphorylcholine

Abstract: Poly(2‐(methacryloyloxy)ethyl phosphorylcholine) (PMPC) is known as a biocompatible polymers. Copolymerization of 2‐(methacryloyloxy)ethyl phosphorylcholine (MPC) and hydrophobic monomers is a general approach that gives bioinert functions to solid materials via the surface coating. However, due to the amorphous nature and super hydrophilicity of the MPC‐based copolymers, both the surface and the mechanical properties are not controlled for biomedical applications. Here, the modulated mechanical property and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…As we reported before, number-average molecular weight (Mn) of all the POSS-MA MPC polymers was in the range of 10 4 , and the POSS-based MPC copolymers were soluble in water 21 .…”
Section: Characterization Of Poss-based Mpc Random Copolymerssupporting
confidence: 52%
See 2 more Smart Citations
“…As we reported before, number-average molecular weight (Mn) of all the POSS-MA MPC polymers was in the range of 10 4 , and the POSS-based MPC copolymers were soluble in water 21 .…”
Section: Characterization Of Poss-based Mpc Random Copolymerssupporting
confidence: 52%
“…It was observed that the CAC value of the copolymers increased with the R groups (C2H5, C6H13, C8H17) in the POSS moiety. Our previous study showed that C2H5-POSS moiety in the Poly MPC matrix increased the hydrophobicity at water-polymer interface 21 . Due to the increased hydrophobicity of C2H5-POSS-MPC, CAC value was found to be lower than the other copolymers.…”
Section: Characterization Of Poss-based Mpc Copolymers Was Performed mentioning
confidence: 98%
See 1 more Smart Citation
“…Based on those perspectives of the MPC-based amphiphilic copolymers, this study focused on the MPC as a hydrophilic monomer as well as the chemical structure of hydrophobic monomers, because the BMA part of poly[MPC- co -BMA] as mentioned above is not optimized for controlling the interaction with PTX. In a previous study, a random copolymer was synthesized by using the MPC and ethyl (C 2 H 5 ) group-modified polyhedral oligomeric silsesquioxane (POSS) methacrylate (MA) as a hydrophobic monomer [18]. The obtained copolymer (MPC- ran -C 2 H 5 -POSS; Figure 1a) was not cytotoxic [18], and it formed a hydrophobic domain in water through the hydrophobic interaction of the C 2 H 5 -POSS moiety.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, a random copolymer was synthesized by using the MPC and ethyl (C 2 H 5 ) group-modified polyhedral oligomeric silsesquioxane (POSS) methacrylate (MA) as a hydrophobic monomer [18]. The obtained copolymer (MPC- ran -C 2 H 5 -POSS; Figure 1a) was not cytotoxic [18], and it formed a hydrophobic domain in water through the hydrophobic interaction of the C 2 H 5 -POSS moiety. In addition, it was found that the tight interaction between the C 2 H 5 -POSS and PTX was correlated with the slow release of PTX from a micelle-like assembly of MPC- ran -C 2 H 5 -POSS [19].…”
Section: Introductionmentioning
confidence: 99%